A method for the risk assessment of biomechanical overload in hospital physiotherapists - Sala, Emma; Bisioli, Andrea; Ponzoni, Pietro; De Bellis, Alessandro; Paraggio, Emilio; De Palma, Giuseppe (La Medicina del Lavoro, 2022)
ABSTRACT Background: In physiotherapists, biomechanical overload risk assessment (RA) is particularly complex due to the tasks’ variability. The present study aims to propose a new methodology, named Whole Body RA Biomechanical Overload (WB-RAMBO), to assess the risk in the activities performed by physiotherapists. Methods: Each type of intervention was broken down into elementary operations. The risk factors (force, repetitiveness, and incongruous postures) were recorded and evaluated for each of these. For each task, the risk level was obtained by integrating the results of multiple ergonomic methods among those proposed by the international literature. To verify and validate the obtained results, we reviewed the medical records of health surveillance carried out on physiotherapists. Results: From the ergonomic point of view, RA shows a situation of acceptability. The observed slight dysergonomies are diluted in the work shift and allow an optimal functional recovery of the musculoskeletal system. Conclusions: This method proposes a RA for each operation performed. A work plan subjected to such a peculiar RA can be redesigned and adapted to the company’s and the hypersusceptible worker’s organizational needs.